Review on the Effects of Chemical Compounds Toxicity on Workers in Chemical Laboratories. - Nagham Mahmood; Sabrean Farhan Jawad (International Journal of Toxins and Toxics, 2026)
Chemical laboratories are considered high-risk work environments due to the wide range of chemicals that workers handle, which may be toxic, corrosive, or flammable. Improper handling of these substances can lead to serious health problems, ranging from mild irritation to death in cases of exposure to chemical compounds such as phenols and amines, which cause various types of lung and laryngeal cancers and respiratory diseases in laboratory workers who are in direct contact with hazardous laboratory materials. Inhaling the fumes of some gaseous substances can lead to pneumonia, chronic bronchial allergies, and difficulty breathing. Some chemicals are irritants to the respiratory membranes and skin, causing short-term symptoms upon exposure, such as inflammation, rashes, redness, allergic reactions, bleeding, or coughing. These symptoms can affect the skin, eyes, and respiratory system. Irritants also damage the ozone layer and thus pose a risk to public health. Examples include chlorine, ammonia, sulfur dioxide, poison ivy, chromic acid, and nickel chloride. There are organic compounds that cause skin erosion or skin irritation upon contact; these are known as corrosive substances. These chemicals lead to the erosion or destruction of the part they come into contact with, such as skin, which can suffer severe burns and tissue damage if exposed to any of these substances. Examples of corrosive substances include sodium hydroxide, acetic acid, hydrochloric acid, bromine, and perchloric acid. From all of this, we can conclude that chemical hazards in the workplace, whether in a laboratory or a chemical plant, are threats arising from the presence of chemicals that may cause health and environmental damage, such as fires and explosions, and expose workers to harm such as irritation, burns, and respiratory distress. Types of chemical hazards include flammable, irritant, carcinogenic, explosive, toxic, and other substances. To avoid these hazards, employees must be educated, protective equipment provided, safety labels used, and materials stored correctly.
Keywords: corrosive; flammable; hazardous materials; toxic; toxicity of chemicals